Efficacy and Safety of Glecaprevir/Pibrentasvir in HCV Patients With Previous Direct-Acting Antiviral Therapy Failures: A Meta-Analysis - Shen, Chao; Fan, Haozhi; Ge, Zhijun; Cai, Weihua; Shao, Jianguo; Dong, Chen; Xue, Hong; Fu, Zuqiang; Li, Jun; Zhang, Yun; Yue, Ming (Frontiers in Medicine, 2020)
Background: Since a greater number of hepatitis C virus (HCV) patients have access to direct-acting antiviral (DAA) based therapies, the number of patients not properly responding to prior DAA regimens is increasing. The objective of this comprehensive analysis was to assess the efficacy and safety of glecaprevir/pibrentasvir (GLE/PIB) in HCV patients who experienced previous DAA therapy failures. Methods: Bibliographic databases were systematically searched for relevant articles published by November 2020. The main endpoints were sustained viral response after 12 weeks (SVR12), adverse events (AEs; any grade) and severe adverse events (SAEs). Publication bias assessment was performed using funnel plots and the Egger’s test. Results: Fourteen studies consisting of a total of 1294 subjects were included in this study and the pooled estimate of SVR12, AEs and SAEs rates were 96.8% (95%CI: 95.1-98.2), 47.1% (95%CI: 26.0-69.3) and 1.8% (95%CI: 0.7-3.4), respectively. Subgroup analysis showed that pooled SVR12 rates were 97.9% (95%CI: 96.7-98.9) for Japan and 91.1% (95%CI: 87.3-94.3) for the United States; 95.8% (95%CI: 93.9-97.4) for genotype (GT)1 and 100.0% (95%CI: 99.6-100.0) for GT2; 95.3% (95%CI: 92.4-97.2) for cirrhosis and 96.3% (95%CI: 94.2-97.7) for non-cirrhosis cases. There was no publication bias included this study. Conclusion: This comprehensive analysis revealed that GLE/PIB is an effective and secure retreatment option for patients who did not optimally respond to DAA treatment, especially the Asian population with GT1-2.